A Revisited Inquiry: A Survey of the Members of the American Rehabilitation Counseling Association (ARCA). (January 2019) - Huber, Mary J.; Walker, Quiteya D.; Dunlap, Paige N.; Russell, Valerie E.; Richardson, Taryn V.
In recognition of the American Rehabilitation Counseling Association's (ARCA) 60th anniversary and the need to gather and provide data to further inform the rehabilitation counseling (RC) field with recent developments, a replication of the Peterson, Hautamaki, and Hershenson (2006) study that included surveying ARCA members at the time as well as similar studies in the field (Trotter & Kozochowicz, 1970) was completed. Similar questions related to overall membership benefits, motivations, concerns, and future directions for the field were duplicated. In addition, given the recent major changes in the field including the merger between the Council for Accreditation of Counseling and Related Educational Programs (CACREP) and the Council on Rehabilitation Education (CORE) and the new Clinical Rehabilitation Counselor (CLRC) degree were included. Similar to the 50th anniversary survey, the results of the study informed the ARCA leadership in their future strategic planning activities, organizational development, and in better meeting the needs of ARCA members.